Towards to an Integrative and Integrated Hospital Psychology: The Department of Health and Clinical Psychology of Hospital CUF Tejo - Torrado, Marco (Gazeta Médica, 2023)
Psychology is recognized as an autonomous technical-scientific area, evidence-based, particularly involved in the promotion of global health, prevention and treatment of psychological disorders, aiming to increase health gains. Its integration into the different levels of care has been progressive, meeting standards of quality, effectiveness, equity, guaranteeing the safety of citizens and respect for human rights. Hospitals constitute one of the most important health care environments where clinical and health psychology has expanded as a specific career. This article reviews the historical path of Psychology integration in hospital care, its identity construction, and the specificity of its actions in several clinical domains, supporting a close articulation with medical and non-medical specialties and various fields of scientific knowledge. Some of the main future challenges in this area of knowledge are discussed, with a view of maximizing mental health protective factors and mitigating vulnerabilities in specific groups.